Pengaruh Modal Intelektual dan Pengungkapannya Terhadap Nilai dan Kinerja Perusahaan - Gatot Ahmad Sirojudin; Ietje Nazaruddin (Universitas Muhammadiyah Yogyakarta, Indonesia, 2014)
The aim of this study is to analyze the effect of intellectual capital and intellectual capital disclosures on corporate value and performance of the company. The sample used in this study is a company that reported annual reports and ICMD listed on the Indonesia Stock Exchange. The statistical method used is Partial Least Square, with hypothesis testing the value of the t statistic. Result shows that intellectual capital and intellectual capital disclosures have positive and significant impact on value and the company's performance. However, the disclosure of intellectual capital has no significant effect on the company's performance.